Contributions to the knowledge of the “Staphylinus-complex” (Coleoptera: Staphylinidae: Staphylinini) of China. Part 13. The genus Sphaerobulbus Smetana 2003. Section 3 - Smetana, Aleš (Zootaxa, 2006)
This is the third paper dealing with the Chinese species of the genus Sphaerobulbus Smetana, 2003. Two species are described as new: S. biplagiatus (from Yunnan) and S. ornatus (from Shaanxi). New distributional records for S. bisinuatus Smetana, 2003 and S. abdominalis Smetana, 2003 are given. Sphaerobulbus ornatus is the first member of the genus to occur in the province of Shaanxi.